The Impact of International Trade on Indonesia's Economic Growth - Shafa Zhafira Khalid; Zahara Ananda; Darmawan Setia; Layla Hasfajira; Mufqi Aulia Ritonga (ISNU Sumatera Utara, 2025)
Especially in the current era of globalization, international trade is crucial for the economic progress of a country, particularly Indonesia. The purpose of this study is to examine how international trade, encompassing import and export activities, has influenced Indonesia's economic growth in recent years. This study uses a literature review approach to investigate several factors, including exchange rates, the balance of payments, and fiscal and monetary policies, that influence the relationship between economic growth and international trade. The study's findings indicate that while imports help meet demand for commodities that are difficult to produce effectively domestically, export growth has a significant effect on GDP growth. However, heavy reliance on imports can make it difficult to maintain economic stability. Therefore, to optimize the contribution of international trade in driving sustainable Indonesian economic growth, an export diversification strategy and increased competitiveness of domestic products are needed.